Hydroxychloroquine is associated with slower viral clearance in clinical COVID-19 patients with mild to moderate disease. Issue 52 (24th December 2020) - Mallat, Jihad; Hamed, Fadi; Balkis, Maher; Mohamed, Mohamed A.; Mooty, Mohamad; Malik, Asim; Nusair, Ahmad; Bonilla, Maria-Fernanda
Abstract : Abstract: There are conflicting data regarding the use of hydroxychloroquine (HCQ) in COVID-19 hospitalized patients. The objective of this study was to assess the efficacy of HCQ in increasing SARS-CoV-2 viral clearance. Hospitalized adult patients with confirmed SARS-CoV-2 infection were retrospectively included in the study. The primary outcome was the time from a confirmed positive nasopharyngeal swab to turn negative. A negative nasopharyngeal swab conversion was defined as a confirmed SARS-CoV-2 case followed by 2 negative results using RT-PCR assay with samples obtained 24 hours apart. Multiple linear regression analysis was used to adjust for potential confounders. Thirty-four confirmed COVID-19 patients completed the study. Nineteen (55.9%) patients presented with symptoms, and 14 (41.2%) had pneumonia. Only 21 (61.8%) patients received HCQ. The time to SARS-CoV-2 negativity nasopharyngeal test was significantly longer in patients who received HCQ than those who did not receive HCQ [17 (13–21) vs 10 (4–13) days, P  = .023]. HCQ was independently associated with time to negativity test after adjustment for potential confounders (symptoms, comorbidities, antiviral drugs, pneumonia, or oxygen therapy) in multivariable Cox proportional hazards regression analysis (hazard ratio = 0.33, 95% confidence interval: 0.13–0.9, P  = .024). On day 14, 47.8% (14/23) patients tested negative in the HCQ group compared with 90.9% (10/11) patients who did not receive HCQ ( P  = .016). HCQ was associated with a slower viral clearance in COVID-19 patients with mild to moderate disease. Data from ongoing randomized clinical trials with HCQ should provide a definitive answer regarding the efficacy and safety of this treatment. Abstract : Supplemental Digital Content is available in the text